2018
DOI: 10.14744/semb.2017.29491
|View full text |Cite
|
Sign up to set email alerts
|

Value of Tei Index in Predicting Implantable Cardioverter Defibrillator Shocks

Abstract: İ mplante edilen kardiyoverter defibrilatörler (İKD) ani kardiyak arrest ve yüksek riskli kalp hastalığı olanlarda mortalitede azalma sağladıkları bilinen tedavilerdir ve yaygın olarak kullanılmaktadırlar. [1][2][3] Ancak gerçek hayatta İKD şokları, hastanın hayat kalitesi ve psikolojik durumu üzerinde olumsuz etkilere neden olmaktadır. Yapılan çalışmalarda İKD şoklarının sayısı arttıkça hastanın fiziksel ve mental sağlığında düşüş olduğu tespit edilmiştir. [4][5][6][7][8][9] İKD şokları arttıkça hastaların ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In previous studies, the TI was identified as a sensitive tool for diagnosis and risk stratification of patients with heart failure [ 16 , 23 , 24 ], chronic coronary syndrome [ 19 ] and acute myocardial infarction [ 25 , 26 ]. However, despite the promising findings of previous studies, evidence on the clinical aspects of the TI in myocarditis is very scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the TI was identified as a sensitive tool for diagnosis and risk stratification of patients with heart failure [ 16 , 23 , 24 ], chronic coronary syndrome [ 19 ] and acute myocardial infarction [ 25 , 26 ]. However, despite the promising findings of previous studies, evidence on the clinical aspects of the TI in myocarditis is very scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The Tei index before transjugular intrahepatic portosystemic shunt (TIPS) may predict mortality in cirrhotic patients Ref. 29 Seyis et al…”
Section: Cirrhotic Patientsmentioning
confidence: 99%
“…The Tei index predicts ICD shocks easily. 29 The tei-index identifies cardiac function problems in hypertensives with left ventricular hypertrophy after chemotherapy better than echocardiography. 30 The main topic points of recent studies were shown in Table 1.…”
Section: Recent Studiesmentioning
confidence: 99%
See 1 more Smart Citation